Efficient conditional aggregation of encrypted data in tiered sensor networks - Rui LI; Ya-ping LIN; Jin-guo LI (Tongxin xuebao)
A privacy preserving conditional aggregation protocol was proposed that enabled storage nodes to aggregate the data items satisfied sink issued queries correctly while prevented them from revealing both sensor collected data and Sink issued queries.To protect privacy for sensor col data and sink issued queries,an encoding method based on prefix membership verification and bloom filters was proposed to encode both sensor collected data and sink issued queries,which allowed storage nodes process queries correctly without knowing their actually value.Homomorphism encryption method was adopted to encrypt sensor collected data,which enabled storage nodes to process aggregation on encrypted data items.To reduce corresponding energy consumption between sensors and storage nodes,a code table method was proposed to represent and transmit data items.Analysis and experime validate the efficacy and efficiency of the proposed protocol.